On benzenoid systems with minimal number of inlets - Cruz Roberto; Gutman Ivan; Rada Juan (Journal of the Serbian Chemical Society, 2013)
Inlets are features on the perimeter of a benzenoid system that determine numerous of its electronic and topological properties. A class of large benzenoid systems is constructed, having small number of inlets. It is shown that the minimal number of inlets in a benzenoid system with h hexagons is less than or equal to √3(h-1).